The status of paediatric medicines initiatives around the world-what has happened and what has not? - Hoppu, Kalle; Anabwani, Gabriel; Garcia-Bournissen, Facundo; Gazarian, Madlen; Kearns, Gregory L; Ranganathan, Shilani Sri (My University, 2011)
PURPOSE: This review was conducted to examine the current status of paediatric medicines initiatives across the globe. METHODS: The authors made a non-systematic descriptive review of current world situation. RESULTS: Two regions, the United States (US) and the European Union (EU), and the World Health Organization (WHO) have introduced strong paediatric initiatives to improve children's health through improving access to better paediatric medicines. The experience from the US initiative indicates that it is possible to stimulate development and study of paediatric medicines and provide important new information for improvement of paediatric therapy. The early results from the EU initiative are similarly encouraging. In Canada, Japan, Australia and other developed countries, specific paediatric medicines initiatives have been less extensive and weaker, with modest results. Disappointingly, current evidence suggests that results from clinical trials outside the US often do not benefit children in the country in which the trials were largely conducted. Pharmaceutical companies that have derived a financial benefit commensurate with the cost of doing the paediatric trials in one country do not seem to be making the results of these trials available to all countries if there is no financial incentive to the company. The WHO campaign 'make medicines child size' has produced substantive accomplishments in building improved foundations to improve mechanisms that will enhance children's access to critical medicines in resource-limited settings. However, practically all of this work has been performed using an amalgamation of short-term funding from a variety of sources as opposed to a sustained, programmatic commitment. CONCLUSIONS: Although much still needs to be done, it's clear that with concerted efforts and appropriate resources, change is possible but slow. Retaining and fostering public and political interest in paediatric medicines is challenging, but pivotal for success.